Social norms, Power relations, and Negotiations in Decision-Making on the use of Sterilisation by Women Living with HIV in Eastern Uganda: A Qualitative Study - Edith M. Birungi; David Kaawa-Mafigiri; Paul Bukuluki (Eastern African Journal of Humanities and Social Sciences)
Failure to translate women’s desire into increased sterilisation use has been associated with inequitable social norms in patriarchal contexts that grant men control and decision-making authority and relate womanhood to motherhood and child care. This study adopted a multiple case study design to explore the experiences of women living with HIV(WLHIV) in negotiating social norms to implement decisions on getting sterilised. The integrated social-ecological framework was utilised to understand how social norms may intersect with multiple contextual factors to limit or facilitate women’s agency in deciding to end their reproduction. Data were collected using open-ended interviews with fourteen purposefully selected sterilised WLHIV, aged 15-49 years, from two public health facilities in Tororo district. Women’s narratives of contraceptive decision-making experiences were audio recorded, transcribed, and analysed inductively and deductively using thematic content analysis. Results revealed that the decision to get sterilised is complex and influenced by the interaction between social norms and other factors such as access to information about the sterilisation method, health status, social support from family members, peers, and health workers, institutional policies, and the general socioeconomic condition in the country. The study recommends that healthcare providers should enhance the knowledge and skills of WLHIV and their social networks to assert control over inequitable structures and relations of power through a shared decision-making approach to contraceptive counselling. Family planning programmes should also increase access to free sterilisation services.